THEORETICAL DEPENDENCE OF WEAR VALUE OF FRICTION PAIR «CENETR PLATE – CENTER PAD» ON A FREIGHT CAR MILEAGE - Muradian, L. A.; Podosenov, D. O.; Shaposhnyk, V. Y. (Science and Transport Progress, 2017)
Purpose. The paper considers the interaction of the cylindrical surfaces of the friction pair «center plate – center pad» of the freight car and theoretically investigates the wear process. It is also necessary to obtain the wear value dependence of center pad on the mileage, taking into account the power load, the physical-mechanical and tribo-technical properties of the interacting materials for the subsequent modeling and control of the value of overhaul mileage by the wear criterion of the corresponding resource-determining elements of freight cars. Methodology. For theoretical studies of the wear value of friction pair «center plate – center pad» on the freight car mileage, the theory of friction and wear of solids was used. Findings. In this paper interaction of cylindrical surfaces of the friction pair «center plate – center pad» of a freight car in the form of a «shaft-sleeve» model is considered. Dependences of the permanent and variable wear of a given friction pair are proposed for cases in which forces act in the transverse and longitudinal directions. Obtained dependence of the wear value of center pad on the freight car mileage takes into account the power load, physical and mechanical and tribo-technical properties of the conjugated materials. On its basis, using new materials for repair with various properties, one may simulate the wear state of cylindrical surfaces of the friction pair «center plate – center pad», which will make it possible to control the value of overhaul mileage of freight car. Also (on the example of gondola 12-7023) on the basis of obtained expression there were constructed dependences of the average wear value of center pad for the cases of different values of the mileage use coefficient and the train movement speed. It was shown that with an increase in the train speed to 100 km/h, the average wear value of the gondola 12-7023 center pad is lower by 25% than at the speed of 80 km/h. Originality. In the work on the wear criterion, the interaction of cylindrical surfaces of the friction pair «center plate – center pad» of a freight car is considered. For the first time it was obtained the dependence of wear value of center pad on the mileage taking into account the power load, physical and mechanical and tribo-technical properties of the conjugated materials. Applying new materials for repair with different properties, based on the obtained dependence one can carry out a simulation of the wear state of cylindrical surfaces of friction pair «center plate – center pad», that is to control the value of between-repair mileage of freight car. Practical value. The results of the work make it possible to establish the wear value of canter pad for the corresponding operating mileage of the freight car.